Estrogen receptor agonists protect against acetaminophen-induced hepatorenal toxicity in rats - YILDIRIM, ALPER; YEGEN, BERRAK (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
Aims: Acetaminophen-induced hepatorenal toxicity varies among sexes with controversial results among species. The aim was to compare the impact of sex and ovarian hormones on hepatorenal toxicity and to elucidate protective effects of estrogen and estrogen receptor (ER) agonists. Main methods: Under anesthesia, female rats underwent ovariectomy (OVX) or sham-OVX. Starting at postsurgical 40th day, OVX-rats received subcutaneously (each, 1 mg/kg/day) 17 beta-estradiol (E2), ER beta-agonist (DPN) or ER alpha-agonist (PPT) for 10 days, while male and sham-OVX rats received vehicle for 10 days. Then, rats received either acetaminophen (3 g/kg) or saline by orogastric gavage and were decapitated at 24th h. Blood samples were obtained to measure serum ALT, AST, BUN, creatinine levels. Liver and kidney samples were obtained for histopathologic examination and for analyzing levels of luminoland lucigenin-chemiluminescence, glutathione and myeloperoxidase activity. Key findings: Compared to their control groups, levels of AST, ALT, BUN, creatinine, hepatic and renal myeloperoxidase activity and chemiluminescence levels were increased, and hepatic glutathione level was decreased in acetaminophen-administered male groups, while ALT and hepatic chemiluminescence levels were not elevated in sham-OVX-rats. Both ER-agonists and E2 reduced BUN, creatinine and reversed all oxidative parameters in renal tissues of OVX-rats. Additionally, ER alpha-agonist reversed all hepatic injury parameters, while ER beta-agonist elevated hepatic glutathione level. Significance: Acetaminophen toxicity in female rats presented with a more preserved hepatic function, while renal toxicity was not influenced by sex or by the lack of ovarian hormones. Pretreatment with estrogen or ER agonists, via their antioxidant actions, provided protective effects on acetaminophen-induced hepatorenal toxicity.
Keywords: Acetaminophen; Estrogen receptor agonists; Oxidative stress; Hepatorenal toxicity